Prognostic implication of ABC transporters and cancer stem cell markers in patients with stage III colon cancer receiving adjuvant FOLFOX-4 chemotherapy - Han, Song-Hee (Oncol Lett, 2019)
Cancer stem cell (CSC) and ATP-binding cassette (ABC) transporters are associated with treatment resistance and outcomes of patients with cancer. The present study investigated the prognostic implications of pre-therapeutic expression of ABC transporters and CSC markers in patients with colon cancer (CC) who received adjuvant 5-fluorouracil, leucovorin and oxaliplatin combination therapy (FOLFOX-4). The immunohistochemical expression of 3 ABC transporters, including ABC subfamily C member 2 (ABCC2), ABCC3 and ABC subfamily G member 2 (ABCG2), and 3 CSC markers, including sex determining region Y-box 2 (SOX2), leucine-rich repeat-containing G protein-coupled receptor 5 and aldehyde dehydrogenase 1, were determined in 164 CC tissues from patients with stage III CC, who underwent postoperative FOLFOX-4 chemotherapy. The association between the protein expression and patients' prognoses was statistically analyzed. ABCG2 was associated with favorable overall survival rate (OS; P=0.001), and ABCC2, ABCG2 and SOX2 were associated with increased disease-free survival rate (DFS; P=0.001, 0.002 and 0.013, respectively). In multivariate analyses, ABCG2 was an independent prognostic factor for OS [hazard ratio (HR)=2.877; P=0.046], and ABCC2 and SOX2 were independent prognostic factors for DFS (HR=2.831; P=0.014; HR=2.558, P=0.020, respectively). ABCC2, ABCG2 and SOX2 may be promising prognostic markers for patients with CC receiving FOLFOX-4 therapy.